Model Peningkatan Perilaku Caring pada Mahasiswa Jurusan Keperawatan Politeknik Kesehatan Kemenkes Pangkalpinang - Nurhayati, Nurhayati (Politeknik Kesehatan Tanjungkarang, 2018)
The purpose of this study was to establish the model and measurement of caring behavior in the students of Nursing Department Poltekkes Pangkalpinang. The method used is quantitative survey technique in stage I, an experiment by creating a book as a means of experimentation with the design Pretest-Posttest Group Single (The One Group Pretest posttest) for phase II. Followed by a qualitative phase III. A sample size of 69 students (i) level I and level II. The research found that. Variable Compassion (love) influence on the formation of Competention while variable concience (knowledge) and Commitment does not affect the establishment of Competention competence, while the overall variable Compassion (affection), concience (knowledge), Commitment and Competention (competencies) affect the establishment of Caring Behavior (Behavior caring).